KEBERADAAN KONSEP RULE BY LAW (NEGARA BERDASARKAN HUKUM) DIDALAM TEORI NEGARA HUKUM THE RULE OF LAW - Made Hendra Wijaya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
This research titled, the existence of the concept of rule by law (state law) within thestate theories of law the rule of law, which is where the first problem: How can theadvantages of Rule by Law in the theory of law Rule of Law?, How is the dis advantages of aconcept of Rule by law in the theory of law Rule of Law.This research method using the method of normative, legal research that examines thewritten laws of the various aspects, ie aspects of the theory, history, philosophy, comparative,structure and composition, scope, and content, consistent, overview, and chapter by chapter,formality, and the binding force of a law, and the legal language used, but did not examine orimlementasi applied aspects. By using this approach of Historical analysis and approach oflegal conceptual analysis.In this research have found that the advantages of the concept of Rule by Law lies in theproviding of certainty, can also be social control for the community, thus ensuring all citizensin good order at all reciprocal relationships within the community. And Disadvantages of theconcept of Rule by Law if the Law which legalized state action is not supported by democracyand human rights, and the principles of justice, there will be a denial of human rights,widespread poverty, and racial segregation, and if the law is only utilized out by theauthorities as a means to legalize all forms of actions that violate human can inflicttotalitarian nature of the ruling